English Medium Instruction and Identity-formation of Undergraduate Students in Sri Lanka - Jayawardana, H.M.H.N.M. (University of Jaffna, 2025)
In Sri Lanka both the majoritarian language Sinhala and the minority language Tamil are considered official and national languages while English is recognized as the link language. Nevertheless, the status of both the Sinhala and Tamil languages does not always reflect their official recognition in society. English is considered a prominent indicator of class identity. Against this background, this qualitative study focused on identifying how English as a Medium of Instruction (EMI) shapes the identities of Sri Lankan university students. It explored the students’ diverse language ideologies and the role languages play in identity formation. For this purpose, 20 students from two universities in Sri Lanka were interviewed. The sample included the students who are taking EMI courses and those who do not. The data was analyzed thematically. The results of the study revealed that the majority of the students consider English language proficiency as a pathway for professional and academic success aligning with the popular ideology in South Asia and elsewhere. In addition, the study shows how EMI has contributed to shaping individual and group identities reflected in behaviours, fashions, lifestyles, and personalities. It was also revealed that the EMI students are recognized as ‘intelligent’ students compared to the vernacular ones. The study further highlighted how English language proficiency levels could be related to self-confidence as well as self-insecurity among undergraduate students. In conclusion, the study emphasizes that identity sensitive approaches, language policies and supportive instructional strategies should be provided to students in their learning environments while ensuring the promotion of inclusivity and prevention of prejudices connected with identity-related English language phobia.
Keywords: Link language; English medium instruction; Language ideologies; Identity formation; Self-confidence